Foreign overriding mandatory provisions under the regulation (EC) No 593/2008 (Rome I Regulation). Judgment of the European Court of Justice of 18 october 2016, case c-135/15 - Kronenberg, Alexander (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The role and treatment of foreign overriding mandatory provisions in international contract law have been subject to academic discussions for a long time. This has not changed with the introduction of Article 9 of the Rome I Regulation. In the judgment discussed in this case note, the European Court of Justice addressed some of the contentious issues in relation to Article 9(3) of the Rome I Regulation. This note examines and evaluates the solutions found by the ECJ and puts them into context. It also points out some questions the ECJ did not discuss; these questions remain open for now but will need to be addressed in the future.